Attitudes of secondary school teachers in Qasbah Irbid towards developing creative thinking in light of the Corona pandemic and the obstacles facing its implementation - Obaidat, Luai Taleb (Frontiers in Education, 2026)
PurposeThe aim of the current study is to get acquainted with secondary school teachers in Qasbah Irbid towards developing creative thinking in light of the Corona pandemic, and to try to identify the obstacles facing its implementation from the teachers’ viewpoint.Design/methodology/approachThe study adopted the descriptive approach through a questionnaire consisting of (33) items, after verifying its validity and reliability. It was distributed to all secondary school teachers in the Qasbah of Irbid, where (650) male and female teachers responded to it.FindingsThe results of the study were as follows: The average of the secondary school teachers’ attitudes in Qasbah of Irbid towards the development of creative thinking reached an average score of 2.86. There are statistically significant differences in the attitudes of secondary school teachers in Qasbah Irbid towards developing creative thinking due to the gender variable, in favor of males, and there are statistically significant differences due to the variable of qualification, in favor of teachers who hold a bachelor’s degree. There are no statistically significant differences due to the variable of experience. As for the obstacles facing the implementation and application of the development of creative thinking in secondary schools from the teachers’ point of view, they obtained a large degree, with an average of 3.58, and a high degree.Research limitations/implications(1) Objective limits: the attitudes of secondary school teachers in Qasbah Irbid towards developing creative thinking, and the obstacles facing its implementation; (2) Human limits: the responses of a sample of secondary school teachers in Qasbah Irbid; (3) Spatial limits: All secondary schools in Qasbah Irbid; (4)Time limits: the first semester of the academic year 2021/2022 AD.Originally/valueThis study contributes to bridging the gap in trying to identify the obstacles to implementing the development of creative thinking, especially after the Corona pandemic, which greatly affected the educational stage, where the concept of creative thinking became necessary and must be taken to develop the learning process in order to keep pace with the developments that occurred, and what are the difficulties that teachers may face at Schools for its application.